Pelatihan Prophetic Parenting untuk Menurunkan Stres Pengasuhan pada Ibu dengan Anak Disabilitas Tunanetra - Habibah, Ridha; Nashori, H. Fuad; Kumolohadi, Retno (Philanthropy: Journal of Psychology, 2021)
ABSTRACTThis study aims to determine the effect of prophetic parenting training in reducing parenting stress in mothers with children with disabilities. This study involved 7 mothers of children with disability that had parenting stress from the moderate to very high parental stress scores. The seven mothers were divided into two groups, 3 in the experimental group and 4 in the control one. Prophetic parenting training was carried out four times within a two-hour session. Parenting stress was measured using the parenting stress scale from Abidin (Ahern, 2004) adapted by Kurniawan (2012) with a total of 36 items and coefficient Î±=0.82. Pretest were done before training, posttest 1 was done after training, and posttest 2 was done two weeks after training. The result analysis of friedman test showed that score of p=0.043 (p0.05) and postest 2 with the score of p=0.017 (p